Multiple epithelioid hemangioedothelioma of the skull in a child: A case report. Issue 30 (July 2016) - Zhu, Ying; Fan, Miao; Pandey, Sagar; Liang, Wei; Chang, Dandan
Abstract: Introduction: Epithelioid hemangioedothelioma (EHE) is a rare vascular tumor characterized by neoplastic proliferation of epithelioid or histiocytoid epithelial cells. EHE of bone constitutes <1% of primary malignant bone tumor. EHE in the skull is an extremely rare case. Here, we report a case of multiple neoplasm of the skull in a 15-month-old boy who presented with gradual facial swelling for 2 months. On computed tomography (CT) scan, multiple irregular osteolytic lesions were seen on the right maxillary, sphenoid, left zygoma, and roof of the left orbit. Excisional surgery of the lesion was planned. Histopathological and immunohistochemical examination of excised specimen suggest it to be epithelioid hemangioedothelioma. Follow-up for 6 months showed no recurrence. Conclusion: Epithelioid hemangioedothelioma is a locally aggressive tumor with metastatic potential. CT imaging could help in assessment of lesion, but final diagnosis is possible only with histopathology. Complete surgical resection at the early stage of the disease is the most effective treatment with better prognosis.